Penrose and Steindl: Foundations for a general theory of firms and competition - Bloch, Harry (School of Economics and Finance, Curtin Business School, 2005)
Edith Penrose and Josef Steindl each developed a distinctive analysis of the growth of firms. They undertook to understand the process that was leading to increasing dominance of industry, particularly manufacturing industry, by a small number of large firms. In the present paper, we examine the work of these two authors to detect similarities and differences in the way they deal with the determinants of firm growth and the implications of such growth for the competitive struggle amongst firms.Our particular focus is on the divergent conceptualisations of the notion of capacity between Penrose and Steindl, referring to the quantity and quality of productive services from management with experience within the firm in the case of Penrose and to the quantity and quality of physical assets (particularly machinery) in the case of Steindl. We examine the internal logic of each conceptualisation, as well comparing motivations and implications. Our appraisal is that they both provide coherent, but partial, explanations of the forces driving firm growth. We trace the difference in their explanations to different empirical bases motivating each author?s analytical schema. This leads us to suggest an encompassing explanation that focuses on overcoming any of a variety of bottlenecks, including managerial capability, productive capacity and market development, which can impede a firm?s ability to grow.